(untitled) (Medico Legal Update, 2021)
The border area is one area that needs government attention. The study was aimed at analyzing disparities in hospital use in Kalimantan based on the border-non-border area category. The study was conducted using data from the 2013 Indonesian Basic Health Survey. With the multi-stage cluster random sampling method, 69,043 respondents were obtained. In the final stage, a Multinomial Logistic Regression test was performed to determine any disparities. The study results found that the utilization of inpatient at the hospital for those living in the border area has a probability of utilization of 0.653 times compared to those who live in nonborder areas. Those who live in the border have a lower chance than those who live in non-border areas of using inpatient hospital. The results of the study also found 8 other predictors that influence hospital utilization among adults in Kalimantan Island, Indonesia. The eight predictors are the type of place of residence, marital, education, work type, socioeconomic, health insurance, travel time, and transportation cost. It could be concluded that there was a disparity in hospital utilization in the border–non-border areas in Kalimantan Island, Indonesia. Those living in border areas have a lower likelihood of inpatient utilization than those living in non-border areas.